Adaptation to Bleaching: Are Thermotolerant Symbiodiniaceae Strains More Successful Than Other Strains Under Elevated Temperatures in a Model Symbiotic Cnidarian? - Newkirk, Casandra R.; Frazer, Thomas K.; Martindale, Mark Q.; Schnitzler, Christine E. (Frontiers in Microbiology, 2020)
The ability of some symbiotic cnidarians to resist and better withstand stress factors that cause bleaching is a trait that is receiving increased attention. The adaptive bleaching hypothesis postulates that cnidarians that can form a stable symbiosis with thermotolerant Symbiodiniaceae strains may cope better with increasing seawater temperatures. We used polyps of the scyphozoan, Cassiopea xamachana, as a model system to test symbiosis success under heat stress. We sought to determine: (1) if aposymbiotic C. xamachana polyps could establish and maintain a symbiosis with both native and non-native strains of Symbiodiniaceae that all maintain different tolerances to heat, (2) whether polyps with these newly acquired Symbiodiniaceae strains would strobilate (produce ephyra), and (3) if thermally tolerant Symbiodiniaceae strains that established and maintained a symbiosis exhibited greater success in response to heat stress (even if they are not naturally occurring in Cassiopea). Following recolonization of aposymbiotic C. xamachana polyps with different strains, we found that: (1) strains Smic, Stri, Slin and Spil all established a stable symbiosis that promoted strobilation and (2) strains Bmin1 and Bmin2 did not establish a stable symbiosis and strobilation did not occur. Strains Smic, Stri, Slin, and Spil were used in a subsequent bleaching experiment; each of the strains was introduced to a subset of aposymbiotic polyps and once polyp tissues were saturated with symbionts they were subjected to elevated temperatures - 32°C and 34°C - for two weeks. Our findings indicate that, in general, pairings of polyps with Symbiodiniaceae strains that are native to Cassiopea (Stri and Smic) performed better than a non-native strain (Slin) even though this strain has a high thermotolerance. This suggests a degree of partner specificity that may limit the adaptive potential of certain cnidarians to increased ocean warming in the future. We also observed that the free-living, non-native thermotolerant strain Spil was relatively successful in resisting bleaching during experimental trials. This suggests that free-living Symbiodiniaceae may provide a supply of potentially ‘new’ thermotolerant strains to cnidarians following a bleaching event.